Investigating The Role of Housing Reconstruction in Healing Traumatic Consequences of a Disaster; TheCase ofthe 2003 Bam Earthquake - Saeedeh Assadi; Ali Sharghi; Zoheir Mottaki; Bahram Saleh Sedghpour (صفه)
A place-based and destructive phenomenon, earthquakes lead to stressful experiences of variouskinds, and a wide range of traumatic consequences for survivors, accompanied by profound changes in the cognitive network and emotional bonds to the concept of house as a safe haven. The long-term impacts of such experiences and perceptions appear in the survivor-home relationships and survivors' recovery. Using the Grounded Theory and based on the long-term lived experiences of the 2003 Bam earthquake survivors in reconstructed houses, the present study investigates survivor-home relationships. The aim is to extract the categories that mitigatetraumatic consequences of an earthquake and promote healing. Based on the findings of 23 in-depth and semi-structured interviews by purposive sampling method and the findings in focus groups of three to five participants, 370 open codes (concepts), 91 main concepts and seven sub-categories in axial coding, and 10 main categories in selective coding were identified. According to the findings, the experience of earthquakesathome causes fears of being trapped in closed and small spaces, of being in spaces with high ceilings and of being in upper floors. The reassurance of the safety of reconstructed houseswere sought in features that support vulnerability mitigation measures and protective behaviour, such as ensuring the possibility of evacuation due to openness and legibility of living spaces, trust in structural safety and construction technology and avoiding vulnerable materials, techniques and features of pre-earthquake houses.Furthermore, the effective housing reconstruction accelerating and restoring the community's dignity were found effective in healing and recovery.On the other hand, the concepts of place attachment and satisfaction were found to be interventive in facilitating this process.According to the results, the nature of the earthquake and the following experiences at home, leads to the formation of collective cognitive-behavioural mentalities in the living environment, and this in turn helps achieving a betterunderstandingof collective healing.